Microglial activatory (immunoreceptor tyrosine‐based activation motif)‐ and inhibitory (immunoreceptor tyrosine‐based inhibition motif)‐signaling receptors for recognition of the neuronal glycocalyx. Issue 1 (21st May 2012) - Linnartz, Bettina; Neumann, Harald
Abstract Microglia sense intact or lesioned cells of the central nervous system (CNS) and respond accordingly. To fulfill this task, microglia express a whole set of recognition receptors. Fc receptors and DAP12 (TYROBP)‐associated receptors such as microglial triggering receptor expressed on myeloid cells‐2 (TREM2) and the complement receptor‐3 (CR3, CD11b/CD18) trigger the immunoreceptor tyrosine‐based activation motif (ITAM)‐signaling cascade, resulting in microglial activation, migration, and phagocytosis. Those receptors are counter‐regulated by immunoreceptor tyrosine‐based inhibition motif (ITIM)‐signaling receptors, such as sialic acid‐binding immunoglobulin superfamily lectins (Siglecs). Siglecs recognize the sialic acid cap of healthy neurons thus leading to an ITIM signaling that turns down microglial immune responses and phagocytosis. In contrast, desialylated neuronal processes are phagocytosed by microglial CR3 signaling via an adaptor protein containing an ITAM. Thus, the aberrant terminal glycosylation of neuronal surface glycoproteins and glycolipids could serve as a flag for microglia, which display a multitude of diverse carbohydrate‐binding receptors that monitor the neuronal physical condition and respond via their ITIM‐ or ITAM‐signaling cascade accordingly. © 2012 Wiley Periodicals, Inc.